NIAT DAN AKTIVITAS BELANJA ONLINE : PENGUJIAN TERHADAP KUALITAS SITUS WEB DAN KEPERCAYAAN - Christian Daniel Manu (Journal of Management Small and Medium Enterprises (SMEs), 2016)
Website has been online business environment that makes transactions is easy to completed. Thequality of the website should be a concern for companies that do online business. Individual whoshop online have the expectation that the quality of the website must be trusted and able to reduceindividual risk perception in the transaction. The theory of planned behavior and technologyacceptance model used as basic theories in the proposed development of a model for measuring theactivity of online shopping.A total of four constructs used in this research model. Constructs ofonline shoppingis expected to be affected by intention to shopping. Then, construct intention toshopping is predicted to be affected by website quality and trust. The 661 data obtained through anonline survey was used to test the model by using a statistical tool Structural Equation Modeling(SEM). The findings of this study indicate that the developed model is marginal fit to explain theinfluence of website quality on intentions and activities of online shopping, with the trust as amediator. Development of website features is the implications of this research.Keywords: Theory of Reasoned Action, Technology Acceptance Model, Website Quality, Trust,Intention, Online Shopping.